SISTEM PENGEMBANGAN AGRIBISNIS HORTIKULTURA BERKELANJUTAN DAN BERDAYA SAING TINGGI DI KAWASAN TIMUR INDONESIA - ANTARA, MADE (SOCA: Jurnal Sosial Ekonomi Pertanian; Vol. 1, No. 2 Juli 2001, 2012)
To develop the Indonesia East Region (KTI) in second long-term development (PJP II) is a necessary and can not delayed again after marginalized in first long-term development (PJP I). Yet, development of Indonesia east region must be based on comparative and competitive advantage and orientation on national and regional importance (province, district) region mentioned. Agribusiness of horticulture with growth engine of ‘on-farm agribusiness’ is main alternative developed in Indonesia east region, cause supported by natural resources, human resources, social capital and the other natural comparative. Then, agribusiness hoped to be growth motor for regional and national economy. To develop the horticulture agribusiness in Indonesia east region (KTI) should be use concept of sustainability horticulture agribusiness development. Its mean, use the natural resources (land, forestry, water) and man made resources (fertilizer, technology, etc) with lower intensity, so there are preservation of natural resources, even increase its quality to heritage for next young generation. To reach the high competitiveness of agribusiness products in Indonesia east region are to step aside of substance and organization constraints, to overcome the problems faced by agribusiness man, to make small the weakness, and to increase role of government and other involve institution to facilitate development of agribusiness in Indonesia east region. To obtain the success of agribusiness development in Indonesia east region, let study from the success story of Thailand agribusiness development (good can be imitated). The success export of Thailand agribusiness products is result of handwork for many years who involve many agents and stakeholders, from king or princess until agribusiness workers, from lecturer or researchers until general community, and from government or finance institution till entrepreneurships. All of this effort continuously always markets oriented. Most important is activity of agents directly support of agribusiness export, like Thailand Airways Cargo.
Keywords: Agribusiness of Horticulture, Sustainability, High Competitiveness, Indonesia East Region